2012
DOI: 10.1038/npp.2012.264
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin 2A Receptors, Citalopram and Tryptophan-Depletion: a Multimodal Imaging Study of their Interactions During Response Inhibition

Abstract: Poor behavioral inhibition is a common feature of neurological and psychiatric disorders. Successful inhibition of a prepotent response in ‘NoGo' paradigms requires the integrity of both the inferior frontal gyrus (IFG) and the serotonergic system. We investigated individual differences in serotonergic regulation of response inhibition. In 24 healthy adults, we used 18F-altanserin positron emission tomography to assess cerebral 5-HT2A receptors, which have been related to impulsivity. We then investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 64 publications
4
43
1
Order By: Relevance
“…A previous fMRI study assessing brain activation after ATD administration during response inhibition revealed serotonergic modulation of the right inferior PFC during inhibitory motor control (Rubia et al, 2005). Macoveanu et al (2013) showed that activation of the left inferior frontal gyrus (IFG) was greater after the administration of the SSRI citalopram than after an ATD challenge during No-Go trials. NoGo responses were larger after ATD administration in the right IFG in subjects with low neocortical 5-HT 2A BP p receptor binding and reduced in those with high 5-HT 2A BP p receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…A previous fMRI study assessing brain activation after ATD administration during response inhibition revealed serotonergic modulation of the right inferior PFC during inhibitory motor control (Rubia et al, 2005). Macoveanu et al (2013) showed that activation of the left inferior frontal gyrus (IFG) was greater after the administration of the SSRI citalopram than after an ATD challenge during No-Go trials. NoGo responses were larger after ATD administration in the right IFG in subjects with low neocortical 5-HT 2A BP p receptor binding and reduced in those with high 5-HT 2A BP p receptor binding.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the left inferior frontal gyrus during nogo was greater with citalopram administrations than with acute tryptophan depletion [37]. The inferior frontal gyrus during nogo trials displayed an interaction between type of 5HT challenge and neocortical 5HT 2A receptor binding, such that acute tryptophan depletion produced an increase in response during nogo trials in right inferior frontal gyrus in subjects with low 5HT 2A binding potential and a decrease in nogo response in those with high 5HT 2A binding potential as measured by positron emission tomography (PET) [37]. Taken together, findings suggest that there may be an optimal level of serotonin, or activation of the 5HT 2A receptor subtype, which allows for successful nogo responses.…”
Section: Underlying Neurocircuitry Of Impulsivitiesmentioning
confidence: 99%
“…Functional MRI (fMRI) in conjunction with various pharmacological challenges of the 5-HT system has been obtained with emotional faces task (Grady et al, 2013;Hornboll et al, 2013) or a gambling task (Macoveanu et al, 2013b, Macoveanu et al, 2013cMacoveanu et al, 2013a). fMRI has also been investigated in relation to genotype (Fisher et al, 2012) and bright light intervention .…”
Section: Introductionmentioning
confidence: 99%
“…Apart from standard screening blood tests, there are for some cohorts biochemical measures of serum brain derived neurotrophic factor (BDNF) (Klein et al, 2010;Trajkovska et al, 2007;Trajkovska et al, 2008), amino acids (Macoveanu et al, 2013a), and sex steroid hormones . In a large proportion of the Cimbi cohort saliva samples have been acquired overnight for determination of cortisol awakening response …”
Section: Introductionmentioning
confidence: 99%